Actaea racemosa L. Is More Effective in Combination with Rhodiola rosea L. for Relief of Menopausal Symptoms: A Randomized, Double-Blind, Placebo-Controlled Study - Lali Pkhaladze; Nina Davidova; Archil Khomasuridze; Ramaz Shengelia; Alexander G. Panossian (MDPI AG, 2020)
Background: The aim of this study was to assess the efficacy and safety of a new herbal preparation (Menopause Relief EP®), the hybrid combination of Actaea racemosa L. (black cohosh, BC) and Rhodiola rosea L. (RR) root extracts, compared with the most effective dose of BC extract in women with menopausal complaints. Methods: A total of 220 women were randomly assigned to receive two capsules either BC (6.5 mg), BC500 (500 mg), Menopause Relief EP® (206,5), or placebo once per day for 12 weeks. The efficacy endpoints were relief of menopausal symptoms, measured using the Kupperman Menopausal Index (KMI), Menopause Relief Score (MRS), and menopause Utian Quality of Life (UQOL) index. Results: The menopause symptom relief effects of RR-BC were significantly superior in all tests to the effects of BC and placebo after their repeated administration for 6 and 12 weeks. There was no statistically significant difference between the effects of BC and BC500 over time. RR-BC significantly improved the QOL index in patients, compared to BC, BC500, and placebo, mainly due to the beneficial effects on the emotional and health domains. Conclusions: BC is more effective in combination with RR in relief of menopausal symptoms, particularly psychological symptoms.